Spontaneous remission without progression to limbic encephalitis in a patient with LGi1 seropositive faciobrachial dystonic seizure - Ahmad, S.B.; Abdullah, S.; Tan, C.T.; Lim, K.S.; Goh, K.J. (ASEAN Neurological Association, 2016)
Faciobrachial dystonic seizures are pathognomonic of leucine-rich glioma inactivated-1 (LGi1) antibody, non-paraneoplastic limbic encephalitis. Faciobrachial dystonic seizures usually precede limbic encephalitis by about a month. It is unknown whether, if untreated, faciobrachial dystonic seizures inevitably progress to limbic encephalitis. We present an LGi1 seropositive patient with a year’s history of faciobrachial dystonic seizures, who achieved remission spontaneously without immunotherapy or antiepileptic drug treatment, and did not develop evidence of limbic encephalitis over a three-year follow-up.